Cryogel Micromechanics Unraveled by Atomic Force Microscopy‐Based Nanoindentation. Issue 11 (14th April 2014) - Welzel, Petra B.; Friedrichs, Jens; Grimmer, Milauscha; Vogler, Steffen; Freudenberg, Uwe; Werner, Carsten
<x xml:space="preserve">Abstract</x> Cell‐instructive physical characteristics of macroporous scaffolds, developed for tissue engineering applications, often remain difficult to assess. Here, an atomic force microscopy‐based nanoindentation approach is adapted to quantify the local mechanical properties of biohybrid glycosaminoglycan–poly(ethylene glycol) cryogels. Resulting from cryoconcentration effects upon gel formation, cryogel struts are observed to feature a higher stiffness compared to the corresponding bulk hydrogel materials. Local Young's moduli, porosity, and integral moduli of the cryogel scaffolds are compared in dependence on gel formation parameters. The results provide valuable insights into the cryogelation process and a base for adjusting physical characteristics of the obtained cryogel scaffolds, which can critically influence the cellular response.